Morphometric Analysis and Genetic Relationship of Rasbora spp. in Sarawak, Malaysia - Aimi Wahidah, Aminan; Leonard Lim, Whye Kit; Chung, Hung Hui; Badiozaman, Sulaiman (Penerbit Universiti Sains Malaysia, 2020)
The genus Rasbora is one of the most species-rich genus among the freshwater fishes and cryptic diversity has been a major hindrance in species identification in the past four decades due to their high similarities in terms of morphology. This study aimed to investigate this issue both morphologically and molecularly. In this study, a total of 23 morphometric parameters were used to differentiate the 103 Rasbora fish samples harvested from different regions of Sarawak state of Malaysia via Multivariate Stepwise Discriminant Function Analysis (SDFA). Then, cytochrome oxidase subunit I (COI) gene was utilised to further distinguish 33 of these fishes, followed by sequence and phylogenetic analysis. Our results unravelled pre-anal length as strongest morphometric discriminant (100%) and that all eight Rasbora species tested are monophyletic except for R. sumatrana and R. caudimaculata, revealing possible cryptic Rasbora species. Further investigations are vital to enrich the data from this study for Rasbora cryptic diversity and conservation studies in future.